Islamic economics and finance instructional leadership and curriculum practices: a case study of selected public universities in Saudi Arabia - Ibrahim, Mohamed Abdeltawab; Abdullah, Arnida; Ismail, Ismi Arif; Asimiran, Soaib (Emerald Publishing Limited, 2023)
Purpose: This study aims to explore the instructional leadership practices implemented by academic professionals and leaders to enhance the curriculum of Islamic economics and finance (IEF) in two public universities in Saudi Arabia. Design/methodology/approach: This study used a qualitative approach, using a case study methodology that focused on two meticulously chosen universities in Saudi Arabia. A total of 21 academics from two public universities in Saudi Arabia who worked in IEF schools were selected for semi-structured interviews. Findings: The findings showed that two universities in Saudi Arabia that offer degrees in IEF exhibited limited instructional leadership. The findings indicate four apparent barriers that may explain the lack of involvement in instructional leadership and fair practices in the IEF curriculum at Saudi Arabian universities. According to this study, a positive collegial climate in Saudi universities’ IEF promotes shared instructional leadership. Research limitations/implications: The use of a limited qualitative method and small sample of respondents in this study may not provide enough evidence to generalise the findings to all universities and higher education schools in Saudi Arabia. Although a case study was used to describe IEF curriculum management and implementation at the two universities, caution should be exercised when applying these findings to other institutions. Practical implications: IEF schools in Saudi universities need to leverage their positive, collaborative and relationship-building environments to develop activities that promote shared instructional leadership. Originality/value: The research findings can offer valuable insights and examples for school leaders to develop instructional activities and promote the concept of “shared instructional leadership”. This approach involves delegating responsibilities and actions to others to enhance the IEF curriculum’s quality. Policymakers and university officials can use these findings to enhance strategic policies.